EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 5 PADANGSIDIMPUAN - Ernawati Mendrofa; Eva Yanti Siregar; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study was to know whether using course review learning model was effective on students’ mathematical problem solving ability on the topic of twovariables linear equation system at the eighth grade students of SMP Negeri 5 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 28 students as the sample and they were taken by using cluster random sampling technique from 259 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using course review learning model was 3.8 (very good category) and (b) students’ mathematical problem solving ability on the topic twovariables linear equation system before using course review learning model was 55.64 (fair category) and after using course review learning model was 81.00 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 17),the result showed the significant value was less than 0.05 (0.049 < 0.05). It means,course review learning model was effective used on students’mathematical problem solving ability on the topic twovariables linear equation system at the eighth grade students of SMP Negeri 5 Padangsidimpuan.